Book Reviews. (1st June 2018) - Sevin, Efe; Froula, Anna; Ruiz-Soler, Javier
Forging the World: Strategic Narrative and International Relations, Alister Miskimmon, Ben O'Loughlin and Laura Roselle (eds) (2018) 1st ed., Ann Arbor: University of Michigan Press, 340 pp., ISBN: 978 0 472 12250 9, e-book, $39.95, ISBN: 978 0 472 13021 4, h/bk, $85.00, ISBN: 978 0 472 03704 9, p/bk, $39.95Zombies, Migrants and Queers: Race and Crisis Capitalism in Pop Culture, Camilla Fojas (2017) 1st ed., Urbana-Champaign, IL: University of Illinois Press, 184 pp., ISBN: 978 0 252 04092 4, h/bk, $95.00, ISBN: 978 0 252 08240 5, p/bk, $24.95, ISBN: 978 0 252 09944 1, e-book, $22.46Decoding the Social World: Data Science and the Unintended Consequences of Communication, Sandra González-Bailón (2017) 1st ed., Cambridge, MA: MIT Press, 256 pp., ISBN: 9780262037075, h/bk, $30.00